Finishing characteristics of heat treated and compressed rubberwood. - Ratnasingam, Jegatheswaran; Ioras, Florin (Springer Verlag, 2013)
The finishing characteristics of heat-treated and compressed Rubberwood were studied. It was found that heat-treated samples had significantly lower finish adhesion strength compared to the conventionally kiln-dried Rubberwood samples, which were used as control specimens. Further, compression of the specimens had also reduced its surface roughness, with an adverse effect on the finish adhesion strength. Inevitably, the use of heat treated and compressed wood in furniture may be suitable for applications, where lower finish adhesion strength could be tolerated at the expense of better finish film quality and process economics, especially in the manufacture of outdoor wooden furniture.